THE USE OF SNAKES AND LADDERS GAMES IN TEACHING VOCABULARY - Titi Rohayati; Andini Sufi Rizkyanti (PROJECT (Professional Journal of English Education), 2019)
The aim of this research is to know the response of students toward the use of snakes and ladders games in teaching vocabulary. To learning vocabulary in English lesson can be fun or bored for students so the purpose of the use this game is that the students can improve their english vocabulary with games method which can make motivate the students to learning. Meanwhile, the observed population that was used for the research was the sixth grade students of SDN 2 Ngamparah Padalarang. The writer used the descriptive qualitative methods. Snakes and ladders games can provide learning motivation to students to always learn or repeat the material that has been studied before which will be tested through games, so that it feels fun for students.